Sejarah Kerajaan Kampung Raja di Desa Tanjung Medan, Kecamatan Kampung Rakyat, Kabupaten Labuhanbatu Selatan - Lasmini, Hera Nurtandina; Daulay, Maraimbang; Siregar, Yusra Dewi (Universitas Nahdlatul Ulama Blitar, 2024)
The main focus of this research problem is the process of discovering a kingdom that once existed in Kampung Raja by analyzing and reconstructing the remains of that kingdom. This kingdom is called the Kampung Raja Kingdom which is located in Tanjung Medan Village, Kampung Rakyat District. This article aims to find out the process of the founding of the Kampung Raja Kingdom, the kings who led the Kampung Raja Kingdom, then the economic, social and political systems, as well as factors in the destruction of the Kampung Raja Kingdom. This research was also carried out for the reason of providing information that there was a kingdom that once existed and existed and had a history and heritage that was worthy of being revealed and its existence known. The type of method used in this research process is the historical research method. Meanwhile, for the approach, the author uses two approaches, namely an archaeological approach and a descriptive qualitative approach. In searching for data, this research uses data collection techniques which consist of three types, namely observation, interviews and documentation. The results obtained from this research are that the Kampung Raja Kingdom was an ethnic Malay kingdom that was founded around 1692 with the first capital in Tanjung Mulia, and experienced a move to Tanjung Medan. The Kampung Raja Kingdom has a royal leadership lineage of five kings. The five kings were Sutan Tua, Sutan Muda, Tengku Sutan Bachludin, Tengku Achmad Putera, and Tengku Nong Hamzah. The Kampung Raja kingdom was destroyed when the social revolution occurred in 1946 in East Sumatra.